2020
DOI: 10.1108/ijoa-12-2018-1608
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of perceived workplace support for small and medium-sized enterprise employees

Abstract: Purpose Perceived workplace support (PWS) is an employee’s perception of perceived organisational support (POS), perceived supervisor support (PSS), perceived co-worker support (PCS) and perceived sufficient resource support (PSRS) to operate effectively. The purpose of this paper is to explore the development and validation of employee’s PWS instrument in small and medium-sized enterprises (SMEs). Design/methodology/approach A total of 15 items of employees’ PWS instrument in SMEs were developed from the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…The survival of small and medium-sized enterprises (SMEs) is critical for a countries’ economic growth (Belsito and Reutzel, 2019; Didonet and Diaz-Villavicencio, 2020; Na-Nan et al , 2019; Na-Nan and Wongsuwan, 2020; Rafiki, 2020). While reviewing the literature, a number of studies were identified that have investigated the effect of the Covid-19 lockdowns on SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The survival of small and medium-sized enterprises (SMEs) is critical for a countries’ economic growth (Belsito and Reutzel, 2019; Didonet and Diaz-Villavicencio, 2020; Na-Nan et al , 2019; Na-Nan and Wongsuwan, 2020; Rafiki, 2020). While reviewing the literature, a number of studies were identified that have investigated the effect of the Covid-19 lockdowns on SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fairlie (2020) realized this outcome at the early phase of the pandmeic, arguing that the number of active small businesses reduced by 22% in the United States between February and April 2020. Other scholars examined the economic impact of financial losses and closures of SMEs during the pandemic by arguing that a country's economic growth largely depends on its SMEs (Belsito & Reutzel, 2019;Didonet & Diaz-Villavicencio, 2020;Na-Nan & Wongsuwan, 2020;Rafiki, 2020). Zafar and Mustafa (2017) echoed this argument by stressing that SMEs in high-income countries contribute to over 55% of GDP and over 65% of total employment, while in low-income nations, their contribution goes up to 60% of GDP and 70% of total employment.…”
Section: Introductionmentioning
confidence: 99%
“…The validation of a scale is a term used to describe the assessment of the psychometric properties of a measure (Na-Nan et al, 2020), where a measure's psychometric properties are statistics that represent its validity and reliability. The validity of a scale has been defined as the degree to which a scale measures what it was designed to measure (Drost, 2011).…”
Section: Scale Validationmentioning
confidence: 99%
“…For instance, if a scale was developed to measure the perceived importance of credit referencing, its validity is the degree to which it measures this variable precisely. On the other hand, reliability is the extent to which a scale can produce consistent results or scores across studies and populations (Na-Nan et al, 2020).…”
Section: Scale Validationmentioning
confidence: 99%
See 1 more Smart Citation